Clinical relevance of molecular characteristics in Burkitt lymphoma differs according to age - Burkhardt, Birgit; Michgehl, Ulf; Rohde, Jonas; Erdmann, Tabea; Berning, Philipp; Reutter, Katrin; Rohde, Marius; Borkhardt, Arndt; Burmeister, Thomas; Dave, Sandeep; Tzankov, Alexandar; Dugas, Martin; et al. (Nature Communications)
While survival has improved for Burkitt lymphoma patients, potential differences in outcome between pediatric and adult patients remain unclear. In both age groups, survival remains poor at relapse. Therefore, we conducted a comparative study in a large pediatric cohort, including 191 cases and 97 samples from adults. While TP53 and CCND3 mutation frequencies are not age related, samples from pediatric patients showed a higher frequency of mutations in ID3, DDX3X, ARID1A and SMARCA4, while several genes such as BCL2 and YY1AP1 are almost exclusively mutated in adult patients. An unbiased analysis reveals a transition of the mutational profile between 25 and 40 years of age. Survival analysis in the pediatric cohort confirms that TP53 mutations are significantly associated with higher incidence of relapse (25 ± 4% versus 6 ± 2%, p-value 0.0002). This identifies a promising molecular marker for relapse incidence in pediatric BL which will be used in future clinical trials.